HUMANISTIC LEARNING THEORY IN ISLAMIC RELIGIOUS EDUCATION WITH A COOPERATIVE LEARNING APPROACH - Irmayanti (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2021)
The purpose of this study is to describe and analyze the Islamic religious education learning with humanistic learning theory with a cooperative learning approach in schools. Learning with humanistic theory aims to foster students' social attitudes and cooperation. The research method used is qualitative with the type of literature. The data sources in the study were taken from journal references, relevant books. The results of this study indicate that the concept of humanistic theory with a cooperative learning approach in Islamic Education learning has significant implications for aspects of student behavior in developing social aspects, cooperation, avoiding bad competition, caring for each other in providing learning assistance at school.